Tolerance of Castor to Soil Salinity - Kumar, D; Daulay, H S; Sharma, P C (Annals of Arid Zone, 2016)
Screening of 16 slrains, of castor (Ricinus communis L.) for salt tolerance in micro-plots, filled with naturally salinized soils of different salinity levels, revealed significant adverse effects of increasing salinity on seedling emergence, plant height, cluster length, sterm girth, 100-seed weight and seed yield. Emergence and seed yield were the most seriously affected traits. exhibiting a reduction of 85.0 and 90.0% at the salinity of 16.0 and 12.5 dS/m at crop sowing and at maturity, respectively, over the control. Strains VI9 and 1379 and the hybrid GCH 4 had lesser extent of decrease in yield, and had higher values of Mean Susceptibility Index (MSI). These strains were, therefore, better tolerant than the rest. Tolerant strains were, in general, marked with more contents of Na and CI in leaf tissue and had lesser reduction of nitrate reductase at ECe 16.0 dS/m corresponding ECe 12.0 dS/m at maturity of the crop.